Efficacy and Role of CT Urography in Investigating Hematuria Among Local Population of Pakistan - Farooq Malik, Muhammad Nauman Iqbal, Tauheed Farid, Safiullah Sohu, Aisha Khalid, Inam Ullah, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Hematuria is a common urologic finding in young adults, reported in 0.3–38.7% of adults in population-based studies. Objectives: The main objective of the study is to find the role of CT urography in investigating hematuria among local population of Pakistan. Material and methods: This descriptive cross-sectional study was conducted in Ganga Ram Hospital, Lahore during June 2020 to July 2021. Fifty patients with hematuria from the hospital OPD provided the data for this study. Results: Most common age group for hematuria was 31-45 years which constituted 41% of the study group and least common age group was 61-75 years constitutes 16%. Thirty-eight women and twelve men took part. Urinary obstruction was caused most frequently by renal, ureteric or both stone disease, which was found in 75.0% of group A patients and 65.0% of those in group B, as shown in table 01. Conclusion: It is concluded that CT urography is useful in detecting urolithiasis, nephrographic phase mostly useful for upper urinary tract pathologies and pyelographic phases are useful for detecting lower urinary tract pathologies.